Health and economic burden due to malaria in Peru over 30 years (1990-2019): Findings from the global burden of diseases study 2019 - Enrique Eduardo Sanchez-Castro; Gladys M. Cahuana; César J. García-Ríos; Clara Guerra-Duarte; Policarpio Chauca; Rafael Tapia-Limonchi; Stella M. Chenet; Bernat Soria; Carlos Chavez-Olortegui; Juan R. Tejedo (Elsevier, 2022)
Summary: Background: Malaria is one of the biggest impediments to global progress. In Peru, it is still a major public health problem. Measures of health and economic burden due to malaria are relevant considerations for the assessment of current policies. Methods: We used estimates from the Global Burden of Diseases Study 2019 for malaria in Peru, grouped by gender and age, from 1990 to 2019. Results are presented as absolute numbers and age-standardized rates with 95% uncertainty intervals (UI). We collected economic data from the World Bank and The National Institute of Statistics and Informatics of Peru and Loreto to calculate the economic burden of productivity loss (EBPL) using the human capital approach. Economic values were presented in constant dollars, soles, and percentages. Findings: Rates of deaths, years of life lost (YLLs), years lived with disability (YLDs), and disability-adjusted life years (DALYs), as well as the EBPL, were drastically reduced from 1990 to 2019. DALYs had a greater percentage of YLDs in 2019 than in 1990. DALYs rates showed no preference between sexes, but the "< 1 year" age group had the highest DALYs values over the study period. We found that the EBPL due to malaria for Loreto was considerably higher than Peru's in terms of GDP percentage. Interpretation: Our study shows that the fight against malaria in Peru reduced remarkably the impact of the disease since 1990; however, during the last decade the estimates were stable or even increased. Our results help to measure the malaria impact on the health status of the Peruvian population as well as the economic pressure that it exerts, constituting remarkable tools for policymaking aimed at reducing the burden of this disease. Strengthening the malaria elimination program is important to achieve the elimination of the disease in the coming years. Funding: This study was supported by the Universidad Nacional Toribio Rodríguez de Mendoza and FONDECYT: Contrato Nº 09-2019-FONDECYT-BMINC.INV and FONDECYT-BM, Perú (Program INCORPORACIÓN DE INVESTIGADORES E038-2019-01, Registry Number: 64007).